Petiolar anatomy of some hitherto unstudied Acanthaceae - Patil, A M; Patil, D A (Journal of Experimental Sciences, 2012)
Anatomy of petioles of 20 species belonging to 12 genera of the family Acanthaceae is investigated.The observations pertain to outline of petiole in T. S., the cell wall contours of epidermis, hypodermis, conjunctive tissue, besides the vascular tissue and cell inclusions, if any. The vascular tissue is generally resolved in an central arc and few vascular bundles. The various anatomical features differ taxon to taxon and hence found useful for their identification.